ACE2 genetic polymorphisms and non-genetic factors were associated with a history of musculoskeletal injuries in high-performance athletes - Lopes, L. R.; Medeiros, R.; Dias, F.; Tavares, V.; Goes, R. A.; de Sousa, E. B.; Machado, D. E.; Perini, J. A. (Journal of Sports Sciences, 2026)
High-intensity exercise affects angiotensin-converting enzyme 2 (ACE2) levels and can modulate regeneration of the skeletal muscle; however, genetic polymorphisms can influence ACE2 expression, which could lead to musculoskeletal injury (MSKi). This case-control study aimed to evaluate the influence of ACE2 polymorphisms, and their combination with non-genetic predictors on the history of MSKi in high-performance athletes. Four hundred eighty-eight athletes genotyped for ACE2 SNPs (rs2285666, rs4240157, and rs2074192). Of the 300 MSKi cases, 51% reported only muscle injuries and 13% only tendinopathy; however, 36% had reported both injuries. The ACE2-rs4240157-T and rs2074192-T alleles, the rs2074192-TT genotype, and the CTT haplotype (rs2285666, rs4240157, and rs2074192) were all associated with an increased risk of MSKi (OR: 1.3; 95% CI: 1.1-1.7; OR: 1.6; 95% CI: 1.2-2.0; OR: 1.7; 95% CI: 1.2-2.5; and OR: 1.4; 95% CI: 1.2-2.0, respectively). Conversely, the ACE2-rs2285666-TT genotype and the TCC haplotype exhibited a protective effect for this condition (OR: 0.4; 95% CI: 0.2-0.9 and OR: 0.6; 95% CI: 0.3-1.0, respectively). The multifactorial score, which included age, sex, BMI, training exposure index, and ACE2 gene SNPs, was significantly higher in MSKi cases compared with controls (p < 0.01). This risk score is important because it has the potential to enhance biostatistical methods of surveillance in athlete health.